Artificial intelligence–driven analysis of antibody and nucleic acid biomarkers for enhanced disease diagnostics - Liu, Zihan; Zhu, Feng; Zhang, Mei (Frontiers in Immunology, 2025)
IntroductionThe rapid evolution of artificial intelligence (AI) technologies has catalyzed a paradigm shift in the landscape of biomarker-driven disease diagnostics, particularly in the context of integrating antibody and nucleic acid indicators. Within this transformative setting, AI offers unprecedented potential for decoding complex molecular interactions across heterogeneous data sources, facilitating early and precise disease identification. However, the effective deployment of AI in this domain mandates enhanced model interpretability, robust cross-domain generalization, and biologically grounded learning strategies—challenges that resonate deeply with contemporary research focused on antibody and nucleic acid diagnostics.MethodsTraditional methodologies for biomarker discovery—such as linear regression, random forests, and even standard deep neural networks—struggle to accommodate the multi-scale dependencies and missingness typical of omics datasets. These models often lack the structural alignment with biological processes, resulting in limited translational utility and poor generalization to new biomedical contexts. To address these limitations, we propose a novel framework that integrates a biologically informed architecture, BioGraphAI, and a semi-supervised learning strategy, adaptive contextual knowledge regularization (ACKR). BioGraphAI employs a hierarchical graph attention mechanism tailored to capture interactions across genomic, transcriptomic, and proteomic modalities. These interactions are guided by biological priors derived from curated pathway databases.ResultsThis architecture not only supports cross-modal data fusion under incomplete observations but also promotes interpretability via structured attention and pathway-level embeddings. ACKR complements this model by incorporating weak supervision signals from large-scale biomedical corpora and structured ontologies, ensuring biological plausibility through latent space regularization and group-wise consistency constraints.DiscussionTogether, BioGraphAI and ACKR represent a step toward overcoming critical barriers in biomarker-driven disease diagnostics. By grounding computational predictions in biological priors and enhancing interpretability through structured embeddings, this framework advances the translational applicability of AI for early and precise disease identification.